4c+6=3c+9

Simple and best practice solution for 4c+6=3c+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4c+6=3c+9 equation:



4c+6=3c+9
We move all terms to the left:
4c+6-(3c+9)=0
We get rid of parentheses
4c-3c-9+6=0
We add all the numbers together, and all the variables
c-3=0
We move all terms containing c to the left, all other terms to the right
c=3

See similar equations:

| 9^-2x=0 | | x/4-1.2=-7.6 | | 26-4x=14+2 | | (x×6)-7=65 | | 11x-32=+8x | | 9x4−21x2=0 | | 11x-32=3-+8x | | 4n-4=5n-10 | | 1.5+0.2x=0.6x-7.3 | | z/10+8=5 | | 7y2+22y-24=0 | | 2/3b+5=10-1b | | -7=3y-4 | | 1.5+0.2=0.6x-7.3 | | 2/3b+5=10-b | | 21-2x=5x+7 | | 841=x^2 | | 18=3(1+12x)=230 | | 5+w/5=-30 | | 3x+2(-x-18)=-30 | | 19=17+4w | | 2x4=98 | | (8x-6)-80=90 | | 3x2=x2+25 | | 4x+9=51 | | 3u+9=60 | | x-4x13=4 | | 11x=x=50 | | (8z-11)(2-z)=0 | | 2/5x-7=12/5x-2x+13 | | 12t-(5t*t)=17 | | −24=-6-6x |

Equations solver categories